"Role" of the Dice: An Exploratory Analysis of Gamer Perceptions and Interpretations of Loot Box Advertising. Issue 1 (2nd January 2021) - Kelling, Kimberly; Tham, Samuel
Abstract: Loot boxes in video games are increasingly becoming focal points in problematic gaming studies; however, few studies have addressed the potential impact on consumers of digital advertising for such loot items. As gaming companies evolve the way in which they promote loot boxes, gamers' sensemaking of loot box promotions must also evolve. This study explores gamer interpretations of promotional messaging among male gamers pertaining to loot boxes within a popular video game ( FIFA 19 ). Findings have significant implications for gaming and persuasion theories. Specifically, we propose a new direction in interactive advertising research grounded in the gamers' in-game role perception.